Non-Hyaluronic Acid Fillers for Midface Augmentation: A Systematic Review - Trinh, Lily N.; Gupta, Amar (Facial Plastic Surgery, 2021)
There has been an increasing role in the use of injectable fillers for rejuvenation of the aging face. In this systematic review, we aim to evaluate the existing literature related to soft tissue fillers of the midface. Specifically, we focus on the non-hyaluronic acid fillers including polymethylmethacrylate (PMMA), poly-L-lactic acid (PLLA), calcium hydroxyapatite (CaHA), and autologous fat. A systematic review was conducted in November 2020 in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with PubMed and Embase databases. Medical Subject Headings terms used were “cheek” OR “midface” OR “malar” and “filler” OR “poly-L-lactic acid” OR “calcium hydroxyapatite,” “autologous fat” OR “polymethylmethacrylate” OR “Artefill” OR “Bellafill” OR “Radiesse” OR “Sculptra.” The initial search identified 271 articles. After 145 duplicates were removed, 126 studies were screened for relevance by title and abstract. A total of 114 studies were eliminated based on inclusion and exclusion criteria. Twelve articles underwent full-text review. Seven articles were included in the final analysis consisting of four non-hyaluronic filler products: PMMA, PLLA, CaHA, autologous fat. Most patients were highly satisfied with their results. Due to the gradual volumizing effects of PMMA, PLLA, and CaHA, patient satisfaction generally improved over time. Minor adverse reactions related to treatment included bruising, swelling, and pain. Nodule formation was reported in PLLA and CaHA studies. For autologous fat, 32% of the original injection volume remained at 16 months post-treatment, which still provided clinically improved malar enhancement. Dermal fillers are an attractive treatment option for the aging face due to their high patient satisfaction, long-lasting effects, and low side-effect profile. Patients should be appropriately counseled on the delayed effects of non-HA fillers. Autologous fat is a good option in many patients with the major drawback of unpredictable longevity, which may require a secondary procedure. Future studies should examine the longevity and long-term side effects of these fillers.
Keywords: facial filler; autologous fat; midface augmentation; cheek; rejuvenation